The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Pd-integrated nanostructured electrode-boosted direct ammonia borane fuel cells with power density of over 700 mW cm−2 - Wenxing Jiang; Yuanting Peng; Qiqi Wan; Endao Zhang; Junbo Hou; Xiaodong Zhuang; Changchun Ke (Chemical Engineering Journal, 2026)

Hydrology Modulates the Microplastics Composition and Transport Flux Across the River–Sea Interface in Zhanjiang Bay, China - Xiaoqing Chen; Peng Zhang; Jing Lu; Yuanting Chen; Jibiao Zhang (Journal of Marine Science and Engineering, 2025)
Estuaries act as significant pathways for plastic waste entry into the oceans, with microplastics (MPs) being intricately influenced by river and coastal hydrodynamics. MPs become entrapped within estuaries during transport, particularly at the river–sea interface, which impacted by tidal fluctuations. However, few studies have examined the role of the impacts of tidal variations on microplastic abundance and export flux at the river–sea interface across contrasting hydrological regimes (dry vs. wet seasons). In this study, we conducted observations to assess MPs abundance, composition, and flux in the Suixi Estuary of Zhanjiang Bay, China The results indicated an overall mean abundance of MPs of 91.1 ± 75.0 items/L, which was linked to tidal variations, decreasing during high tides and increasing during low tides. Transparent color, fibrous shape, and a size range of 100–330 μm were the most prevalent characteristics in water samples. MPs diversity was higher during the wet season compared to the dry season. In addition, the MPs influx was about 1.61 × 109 items/year from the river to the sea across both seasons. Additionally, hydrological regimes, tidal forces, and human activities were identified to influence MPs abundance and flux. This quantitative analysis establishes a mechanistic framework for understanding hydrological impacts on estuarine MPs transport, providing critical baseline data for developing targeted pollution management strategies in coastal ecosystems.

Gut microbiota mediates ambient PM2.5 exposure-induced abnormal glucose metabolism via short-chain fatty acids - Wenpu Shao; Bin Pan; Zhouzhou Li; Renzhen Peng; Wenhui Yang; Yuanting Xie; Dongyang Han; Xinyi Fang; Jingyu Li; Yaning Zhu; Zhuohui Zhao; Haidong Kan; et al. (Journal of Hazardous Materials, 2024)

Machine-learning-assisted hydrogen adsorption descriptor design for bilayer MXenes - Weizhi Tian; Gongchang Ren; Yuanting Wu; Sen Lu; Yuan Huan; Tiren Peng; Peng Liu; Jiangong Sun; Hui Su; Hong Cui (Journal of Cleaner Production, 2024)

Asymmetric phosphorylation integrating host feature and blue thermally activated delayed fluorescence of thiaxanthene S,S-dioxide emitter for efficient heavily doped white organic light-emitting diodes - Yingying Chen; Chao Wang; Peng Ma; Yuanting Guo; Yuetong Liu; Aiqi Dang; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

Activation of the bitter taste sensor TRPM5 prevents high salt-induced cardiovascular dysfunction - Hao Wu; Yuanting Cui; Chengkang He; Peng Gao; Qiang Li; Hexuan Zhang; Yanli Jiang; Yingru Hu; Xiao Wei; Zongshi Lu; Tianyi Ma; Daoyan Liu; et al. (Science China Life Sciences, 2020)